Plastic Surgeons and COVID-19 Pandemic - Dash, Suvashis; Das, Rojaleen; Saha, Shivangi; Singhal, Maneesh (Indian Journal of Plastic Surgery, 2020)
The world is suffering from the unprecedented problem of the COVID-19 pandemic. As healthcare professionals, we face the imminent danger of exposure. For Plastic, Reconstructive and Burn surgeons, safety and smooth functioning of day-to-day work during this pandemic is of the utmost priority. However, it is also our responsibility to stop the human-to-human transmission chain and conserve the medical resources for rational use. The disease has spread throughout the country, and with the number of infections increasing day by day, it is very important to adhere to the safety principles. This document aims to provide some insights into the world of plastic, reconstructive and burn surgeons in the time of the COVID-19 outbreak.
Keywords: healthcare worker safety; COVID-19; pandemic; SARS-CoV-2; plastic surgery services